A PRELIMINARY STUDY OF LOWER SIDE BEAM STRUCTURE ON LONGITUDINAL BRIDGE MODEL - Salim, Mohd Azli; Noordin, Aminurrashid; Mansor, Muhd Ridzuan (2012)
This paper investigated the vibration level on lower side bridge structure model. A wood material is selected as a raw material of Model Bridge. The selection is based on the high strength, high quality and low cost. Laboratory test is conducted to measure the vibration level using Frequency Response Function (FRF). Then, the vibration level of lower side beam structure is determined. A maximum interface mobility and minimum phase angle was finding in this testing and it shown a losing damping value at the starting point of excitation. The mobility is very responsive at the anti resonance frequencies and acts as a dynamic absorber to reduce an impact.